The ratios of dietary non-fibrous carbohydrate (NFC) to neutral detergent fiber (NDF) influence intestinal immunity of rabbits by regulating gut microbiota composition and metabolites - Li, Shuo; Liu, Tingting; Wang, Kun; Li, Chong; Wu, Fengyang; Yang, Xinyu; Zhao, Man; Chen, Baojiang; Chen, Xiang (Frontiers in Microbiology, 2023)
Carbohydrate is the most commonly macronutrient consumed across all phases of the diet and acts as a potential regulator in modulating the gut microbiota in animals. However, the influences of dietary non-fibrous carbohydrate (NFC) to neutral detergent fiber (NDF) in different ratios on gut microbiota, metabolites, intestinal immunity and growth performance have not been fully explored. A total of 135 healthy weaned rabbits (45.1±0.7 d of age) with average body weight of 1.08±0.07 kg was randomly divided into five groups. Under the same other nutrient levels, rabbits were fed diets with NFC/NDF ratio of 0.7 (T1), 1.0 (T2), 1.3 (T3), 1.6 (T4), and 1.9 (T5). During the 28 days experiment, T3 rabbits showed the highest final body weight and the lowest feed to weight ratio than T5 rabbits (P<0.05), but no significant difference with T1 or T2 rabbits. The expression of cecal pro-inflammatory factors IL-1β and TNF-α were increased in the T4 and T5 than those of other groups (P<0.05). Conversely, the tight junction protein (ZO-1, Claudin-1 and Occludin) were decreased to varying degrees in T4 and T5 groups. The pH value in the cecal digesta of T5 rabbits were lower than that of T1, T2 and T3 (P<0.05), while the concentration of volatile fatty acids and propionate were higher than those of T1, T2 and T3 rabbits (P<0.05). In terms of gut microbiota, at the phylum level, the relative burden of Firmicutes and Actinobacteria in T2 rabbits were the highest (P<0.05), and the relative burden of Proteobacteria in T5 rabbits was higher than that of other groups (P<0.05). At the genus level, the relative burden of Ruminococcus was higher in T2 and T3 rabbits than that of other groups, and T5 rabbits has the lowest relative burden of Ruminococcus. Combination analysis showed that cecal metabolites were positively associated with fermentation-related phenotypes and the burden of Firmicutes. (P<0.05). In conclusion, different dietary NFC/NDF ratio can affect intestinal immune responses and growth performance of rabbit, and there was a positive effect when dietary NFC/NDF=1.0~1.3.